Peran Usaha Telur Asin dalam Membantu Ekonomi di Kecamatan Kandangan - Dimas Abdul Aziz; Ahmad Rifki Andika Muhdiyanto; M Wildan Al Hakim; Farid Rizky Akbar; Syahru Ramadhan A.G; Ahmad Fakhruddin Fajrul Islam (Lembaga Pengembangan Kinerja Dosen, 2025)
The purpose of this study was to determine and explain the role of salted egg businesses in helping to improve the economy of the community in Kandangan District. Micro and small businesses such as salted egg production have great potential in contributing to household income and local labor absorption. This study uses a case study method with a qualitative approach. Data were collected through field observations, in-depth interviews with salted egg business actors, and documentation of business activities. The results of the study show that salted egg businesses in Kandangan District are not only the main source of income for some people, but also create jobs, encourage economic independence, and increase the purchasing power of local people. In addition, business actors also show creativity in packaging and marketing products, both conventionally and digitally. This study concludes that salted egg businesses can be one of the driving forces of a sustainable local economy if supported by adequate training, market access, and capital.